(untitled) (Context: Journal of Interdisciplinary Studies, 2023)
The purpose of this study was to preliminary analyze the financial literacy in Bosnia and Herzegovina by considering three main dimensions: interest, inflation, and diversification. The target population was working-age individuals (18–65 years old). By using a cross-sectional questionnaire-based survey, 638 useful responses were collected. The data was presented through a series of descriptive statistics and frequencies. The results present the extent of financial literacy by considering several demographic factors, such as gender, age category, education, and an individual monthly income, as well as a comparative assessment with previous studies. The findings provide evidence of moderate financial literacy in Bosnia and Herzegovina as every third (fourth) respondent was able to answer correctly all three questions addressing financial literacy application (definitions). Similarly, to previous studies, financial literacy depends on the income, education, and age of respondents as well. The study is a pioneer one and extends the literature by examining this important construct within Bosnia and Herzegovina.